From cookies to carrots; the effect of inhibitory control training on children's snack selections. (1st May 2018) - Porter, L.; Bailey-Jones, C.; Priudokaite, G.; Allen, S.; Wood, K.; Stiles, K.; Parvin, O.; Javaid, M.; Verbruggen, F.; Lawrence, N.S.
Abstract: Children consume too much sugar and not enough fruit and vegetables, increasing their risk of adverse health outcomes. Inhibitory control training (ICT) reduces children's and adults' intake of energy-dense foods in both laboratory and real-life settings. However, no studies have yet examined whether ICT can increase healthy food choice when energy-dense options are also available. We investigated whether a food-specific Go/No-Go task could influence the food choices of children aged 4–11, as measured by a hypothetical food choice task using healthy and unhealthy food images printed on cards. Participants played either an active game (healthy foods = 100% go, unhealthy foods = 100% no-go; Studies 1 & 2), a food control game (both healthy and unhealthy foods = 50% go, 50% no-go; Studies 1 & 2) or a non-food control game (sports equipment = 100% go, technology = 100% no-go; Study 2 only) followed by the choice task. In Study 2, food card choices were also measured before training to examine change in choices. A post-training real food choice task was added to check that choices made in the card-based task were representative of choices made when faced with real healthy and unhealthy foods. Overall, the active group chose the greatest number of healthy food cards. Study 2 confirmed that this was due to increases in healthy food card choice in this group only. Active group participants chose a greater number of healthy foods in the real food choice task compared to children in the non-food control group only. The results are discussed with reference to methodological issues and the development of future healthy eating interventions.